(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The most of the time, marine sponges are an invertebrate species found in the tropics, subtropics, and temperate zones of the oceans and seas. They are acknowledged as being among the most important sources of bioactive chemicals, which are found in marine habitats and can then be recovered from those settings. These bioactive chemicals are found in marine environments and can then be extracted from those environments. It is common knowledge that the chemicals that are extracted from these sponges demonstrate a wide range of bioactivities, such as antibacterial activity, anticancer activity, and general cytotoxicity. These bioactivities can be found in the isolated chemicals. In this article, we discuss the bioactive chemicals that have been found in marine sponges and their potential applications. These compounds have the potential to serve as antibacterial, antiviral, and antimalarial agents against human infections as well as fish pathogens in the aquaculture industry. In addition, these compounds may also operate as antifungal agents. Sponge organisms found in the ocean have also been shown to have these chemical compounds. This article discusses the importance of marine sponges to the fields of chemistry, microbiology, cell biology, and molecular biology from a biotechnological standpoint. Researchers of marine natural products have discovered new potential medications as a result of their efforts to exploit the remarkable chemical variety that can be found in sponges.